2021
DOI: 10.1016/j.jag.2021.102503
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of traffic density changes inside Wuhan during the COVID-19 epidemic with GF-2 time-series images

Abstract: In order to mitigate the spread of COVID-19, Wuhan was the first city to implement strict lockdown policy in 2020. Even though numerous researches have discussed the travel restriction between cities and provinces, few studies focus on the effect of transportation control inside the city due to the lack of the measurement and available data in Wuhan. Since the public transports have been shut down in the beginning of city lockdown, the change of traffic density is a good indicator to reflect the intracity popu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 34 publications
(28 reference statements)
0
8
0
Order By: Relevance
“…While the outbreak of COVID-19 pandemic and the subsequent lockdowns arising from it have had a major negative effect on the conditions of economy, the environmental components have been slightly relieved of the great anthropogenic activities pressures, such as vehicle traffic, heat generation and large emissions of various pollutants ( Mahato et al, 2020 ; X. Wu et al, 2020; Chen et al, 2021 , Firozjaei et al, 2021a , Wu et al, 2021a ). Some studies have examined the impact of COVID-19 pandemic lockdowns on urban environmental conditions.…”
Section: Introductionmentioning
confidence: 99%
“…While the outbreak of COVID-19 pandemic and the subsequent lockdowns arising from it have had a major negative effect on the conditions of economy, the environmental components have been slightly relieved of the great anthropogenic activities pressures, such as vehicle traffic, heat generation and large emissions of various pollutants ( Mahato et al, 2020 ; X. Wu et al, 2020; Chen et al, 2021 , Firozjaei et al, 2021a , Wu et al, 2021a ). Some studies have examined the impact of COVID-19 pandemic lockdowns on urban environmental conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The COVID-19 shutdowns locked people at homes and reduced their mobility within cities (Geng et al . 2021; Wu et al . 2021; but see Venter et al .…”
Section: Introductionmentioning
confidence: 99%
“…The COVID-19 shutdowns locked people at homes and reduced their mobility within cities (Geng et al 2021;Wu et al 2021; but see Venter et al 2020b) and thus created a natural experimental condition which could have affected the tolerance of urban animals towards humans (usually quantified as flight initiation or escape distance) in three ways. First, the lack of or reduced human presence during shutdowns might result in decreased animal tolerance to humans and consequently increased escape distances because (a) some studies have reported that animal tolerance decreases on the gradient from heavily human-visited ("disturbed") sites to sites with low human activity (Webb & Blumstein 2005;Mikula 2014) and (b) escape distances of urban birds may also increase if less tolerant individuals and species colonise or at least increase their detectability in human-emptied landscapes (Manenti et al 2020;Gordo et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“… 2021 ; Wu et al. 2021 ) and to estimate the number of emergency ambulance dispatches during a state of emergency (Rashed et al. 2021 ).…”
Section: Review Of the Literaturementioning
confidence: 99%